Orthopaedic surgery of the lower limbs in 49 802 rheumatoid arthritis patients: results from the Swedish National Inpatient Registry during 1987 to 2001. Issue 3 (3rd August 2005) - Weiss, R J; Stark, A; Wick, M C; Ehlin, A; Palmblad, K; Wretenberg, P
Abstract : Objectives: To analyse changes in the rates of hospital admission and use of orthopaedic surgery to the lower limbs in Swedish patients with rheumatoid arthritis between 1987 and 2001. Methods: Data for all rheumatoid patients admitted to hospital between 1987 and 2001 were abstracted from the Swedish National Hospital Discharge Register (SNHDR). The data in the register are collected prospectively, recording all inpatient admissions throughout Sweden. The SNHDR uses the codes for diagnoses at discharge and surgical procedures according to the Swedish version of the International Classification of Diseases (ICD). Results: In all, 49 802 individual patients with rheumatoid arthritis were identified, accounting for 159 888 inpatient visits. Hospital admissions for rheumatoid arthritis decreased by 42% (p<0.001) during the period 1987 to 2001. Twelve per cent of all admissions were for a rheumatoid arthritis related surgical procedure to the lower limbs; those admissions decreased markedly (by 16%) between 1987 and 1996, and by 12% between 1997 and 2001, as did the overall number of rheumatoid arthritis related surgical procedures to the lower limbs during both time periods. Between 1997 and 2001, 47% of all rheumatoid arthritis related surgical procedures were total joint arthroplasties. There was an overall trend towards reduced length of hospital stay after orthopaedic surgery to the lower limbs during the study period. Conclusions: Rates of hospital admission and rheumatoid arthritis related surgical procedures to the lower limbs in Swedish patients with rheumatoid arthritis decreased between 1987 and 2001. This may reflect trends in disease severity, management, and health outcomes of this disease in Sweden.